2001
DOI: 10.1002/mrm.1306
|View full text |Cite
|
Sign up to set email alerts
|

MR microscopy of multicomponent diffusion in single neurons

Abstract: This study examines multicomponent diffusion in isolated single neurons and discusses the implications of the results for macroscopic water diffusion in tissues. L7 Aplysia neurons were isolated and analyzed using a 600 MHz Bruker wide-bore instrument with a magnetic susceptibility-matched radiofrequency microcoil. Using a biexponential fit, the apparent diffusion coefficients (ADCs) from the cytoplasm (with relative fraction) were 0.48 ؎ 0.14 ؋ 10 -3 mm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 24 publications
4
68
1
Order By: Relevance
“…A slight (though not significant) increase of the ADC with echo time in cortical areas was reported in (34). Another study (31) reported an ϳ30% increase of the ADC with echo times between 24 msec and 100 msec. Assuming slow exchange and an intra-/extracellular fraction of 80%/20%, Buckley et al (32) predicted that the intracellular T 2 would need to be about 20 msec to explain the results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A slight (though not significant) increase of the ADC with echo time in cortical areas was reported in (34). Another study (31) reported an ϳ30% increase of the ADC with echo times between 24 msec and 100 msec. Assuming slow exchange and an intra-/extracellular fraction of 80%/20%, Buckley et al (32) predicted that the intracellular T 2 would need to be about 20 msec to explain the results.…”
Section: Discussionmentioning
confidence: 89%
“…Other in vivo studies indicate short T 2 components in human cortex (28) and in rat cortex (29) at 2.0 T. High field studies on single neurons demonstrate that short T 2 in cytoplasm, in the range 29 -42 msec (30,31), is associated with low diffusion in cytoplasm of 0.23 ϫ 10 -3 mm 2 /second (30). These single neuron studies use NMR microscopy so that the regional diffusion and relaxation constants were found directly and not as a result of fitting a model to the compound signal.…”
Section: Discussionmentioning
confidence: 95%
“…Since then, studies aimed at improving our ability to image tissue microstructure have focused on understanding cellular-level diffusion properties by MR microscopy in an effort to inform modeling [79][80][81][82][83][84][85], and modeling aimed at extracting specific cytoarchitectural measures [86,87]. A common limitation of these methods is the requirement for strong gradients.…”
Section: Future Directions For the Fast Kurtosis Techniquesmentioning
confidence: 99%
“…The latter is being pursued by diffusion studies on isolated brain slices [13,14], excised spinal cords [15] and a new red blood cell ghost model [16] on the 750 MHz instrument. SNR is also a paramount issue in our continuing microimaging and spectroscopy studies of isolated single neurons [17,18]. Even though these studies were performed to date at fields of up to 600 MHz, SNR improvements provided by even higher fields increase our ability to explore multicompartmental diffusion within the single cell [16] and to localize subcellular regions for spectroscopic examination [17] under a variety of perturbations.…”
Section: Microimaging and Microcoilsmentioning
confidence: 99%
“…SNR is also a paramount issue in our continuing microimaging and spectroscopy studies of isolated single neurons [17,18]. Even though these studies were performed to date at fields of up to 600 MHz, SNR improvements provided by even higher fields increase our ability to explore multicompartmental diffusion within the single cell [16] and to localize subcellular regions for spectroscopic examination [17] under a variety of perturbations. So far, bench tests and preliminary MR studies demonstrate no significant problems in constructing RF microcoils (solenoids having diameters of less than 1 mm) at 750 MHz.…”
Section: Microimaging and Microcoilsmentioning
confidence: 99%